On Some Varieties of Soluble Lie Algebras (Communications in Mathematical Research, 2021)
In this paper, we study a class of soluble Lie algebras with variety relationsthat the commutator of $m$ and $n$ is zero. The aim of the paper is to consider therelationship between the Lie algebra $L$ with the variety relations and the Lie algebra $L$ which satisfies the permutation variety relations for the permutation $φ$ of $\{3, · · · , k\}$.
Keywords: variety; permutation; nilpotent class.